A qualitative study on traditional healers' perceptions and management of epidermolysis bullosa - Antoinette V. Chateau; Nceba Gqaleni; Colleen Aldous; Ncoza Dlova; David Blackbeard (AOSIS, 2023)
Background: Epidermolysis bullosa (EB) is a rare, incurable genodermatosis causing blisters that can result in multisystemic complications and death. Limited data exists on EB in South Africa. Research indicates that the majority of African patients consult traditional health practitioners (THPs) before seeking allopathic healthcare. Aim: This study aims to understand THPs belief systems, experiences, perceptions and management of EB patients and their families in the social and cultural context to improve the healthcare of EB patients. Setting: The study setting is Nelson Mandela School of Medicine, Durban, and Grey's hospital, Pietermaritzburg, KwaZulu-Natal. Methods: Qualitative in-depth interviews were conducted with 10 THPs. A non-probability, purposive sampling method was used. A two-site qualitative study was guided by interpretative phenomenological analysis. Guba's trustworthiness framework was used to ensure rigour. Results: Three male and seven female THPs were interviewed, including sangoma, inyanga and umthandazi. The integration presented five global themes: (1) THP practices, (2) perceptions of THP, (3) experiences of THP with patients with EB, (4) diagnosis and management plans of THP and (5) vision and role of THPs. There were multiple divergent perspectives among the THPs with the shared African worldview. Conclusion: Understanding THPs belief systems and therapeutic options is crucial for holistic patient management. Knowledge exchange can promote safe healthcare practices and facilitate collaboration between traditional and allopathic health practitioners. Contribution: This is the first study to explore THPs perceptions and practices regarding EB, a rare disease.